Toxoplasma gondii stimulates the behavioural changes of rodents: updated evidence - Che Omar, Siti Shafiyyah; Mohd Moklas, Mohamad Aris; Mohtarrudin, Norhafizah; Osman, Malina (Journal of Medical Biomedical and Applied Sciences, 2018)
In recent years, there have been an increased number of reports in the literatures on animal behavioural changes linked with intracellular protozoan Toxoplasma gondii. Evidence for animal behavioural changes with Toxoplasma gondii infection comes from experimental tests on animal models such as mice and rats. These studies describe the important mechanisms of behavioural changes which involving neuromodulator and neurotransmitter level. Furthermore, behavioural changes also have been identified in human as well as animal models that may also play a role in development of schizophrenia in humans.